Coupling effects of water and fertilization on growth and water use of Coffea arabica seedling - Liu Xiaogang; Xu Hang; Cheng Jinhuan; Jin Longjie; Yang Qiliang; Huang Zhumei (浙江大学学报. 农业与生命科学版)
Water and fertilizer are very important for the growth and yield of Coffea arabica. C. arabica is an agricultural product with unique advantage in Yunnan Province, whose planting area and yield account for 90% of the whole country. However, its yield and quality are restricted because of seasonal drought and soil nutrient deficiency.To investigate the optimal mode of water-saving and high-efficient utilization of water and fertilizer of C. arabica, the coupling effects of water and fertilization on growth and water use of C. arabica were studied by using four irrigation levels, i. e. sufficient irrigation (WS, soil moisture content was 75%-85% of soil field capacity), high water (WH, soil moisture content was 65%-75% of soil field capacity), middle water (WM, soil moisture content was 55% 65% of soil field capacity) and low water (WL, soil moisture content was 45%-55% of soil field capacity), and four fertilizer levels of NPK (total nitrogen was 10%, P2O5 was 30% and K2O was 20%), i. e. high fertilizer (FH, 4.5 g/kg dry soil), middle fertilizer (FM, 3.0 g/kg dry soil), low fertilizer (FL, 1.5 g/kg dry soil) and no fertilizer (FN, 0 g/kg dry soil). A completely design of pot experiments of C. arabica (Kadimu P796, a local variety) was conducted in intellectual control greenhouse from April to November in 2012, in Faculty of Modern Agricultural Engineering, Kunming University of Science & Technology in Kunming, Yunnan, China (102°79′E, 24°09′N). Irrigation was controlled by weighing method. Experimental soil bulk density was 1.2 g/cm3, field capacity (FC) of 24.3% (mass by mass). The temperature range of intellectual control greenhouse changed between 12℃ and 35℃ and air humidity range changed between 50% and 85%.Water-soluble NPK compound fertilizer (total nitrogen was 10%, P2O5 was 30% and K2O was 20%) was applied twice on May 26th and August 26th in 2012. Morphological characteristics (basal diameter, plant height, leaf area, root shoot ratio, root mass ratio and specific leaf area) and biomass accumulation and distribution were measured on November 11th, and daily evapotranspiration was measured on October 14th in 2012, the day before irrigation in vigorous growth period of C. arabica seedling.Results showed that the growth (plant height, basal diameter and leaf area) and biomass accumulation of C. arabica seedling increased with the increase of irrigation and fertilizer, but the effect of fertilizer was inferior to irrigation. Compared with low water (WL) treatment, irrigation could increase biomass accumulation by 59.03%-369.77%, and root shoot ratio and root mass ratio increased with the increase of irrigation slightly. Moderate increase of water and fertilizer could greatly increase biomass accumulation and water use efficiency (WUE) under insufficient water and fertilizer, while marginal benefit significantly decreased while water and fertilizer supply increased under sufficient water and fertilizer. Daily evapotranspiration of C. arabica seedling decreased with the increase of fertilizer slightly, while increased with the increase of irrigation significantly. Compared with low water (WL) treatment, irrigation could increase water use efficiency by 7.39%-128.96%.In conclusion, faster growth and higher WUE could be obtained by high water and middle fertilizer (WHFM, soil moisture content was 65%-75% of soil field capacity and fertilizer was 3.0 g/kg dry soil) simultaneously.